Actively mode-locked diode laser with a mode spacing stability of. (October 2015) - Zakhariash, V.F.; Kashirsky, A.V.; Klementyev, V.M.
Abstract: We have studied mode spacing stability in an actively mode-locked external-cavity semiconductor laser. It has been shown that, in the case of mode spacing pulling to the frequency of a highly stable external microwave signal produced by a hydrogen standard (stability of over an averaging period ), this configuration ensures a mode spacing stability of .